COLLECTION, IDENTIFICATION, MOLECULAR CHARACTERIZATION, AND ANTIOXIDANT ACTIVITY OF NON-GILLED MUSHROOMS COLLECTED FROM NORTH WESTERN HIMALAYAS - Singh, Shaveta; Tripathi, Astha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of present research deals with collection, taxonomic, molecular taxonomy characterization, and antioxidant activity of wild non-gilled mushrooms sample collected from North Western Himalayas. Methods: The wild non-gilled mushroom samples were characterized for micro, morphological properties, and molecular identification. 1,1 diphenylpicrylhydrazyl (DPPH), nitric oxide (NO2), hydrogen peroxide (H2O2), and free radical scavenging assay were used to evaluate the antioxidant properties of selected wild non-gilled mushrooms. Results: The obtained results revealed that on the basis of microscopic and morphological identification all the four non-gilled mushrooms samples were tentatively identified as 2/15 (Auricularia sp.1), 6/15 (Auricularia sp.2), 32/15 (Ganoderma sp.), and 132/15 (Trametes sp.). The colony, mycelial, and basidiospore morphology of fungal isolate were evidence of Basidiomycetes family. All these four non-gilled mushrooms were sequenced. Sequences were submitted to National Center for Biotechnology Information (NCBI), and their accession number was MF770159 (2/15), MF774107 (6/15), MF770158 (32/15), and MF770160 (132/15). The phylogenetic analysis of 18S ribosomal deoxyribonucleic acid (18S rDNA) sequence of four non-gilled mushrooms was compared with other species and identified as Auricularia polytricha, Ganoderma lucidum, Auricularia auricula-judae, and Trametes elegans. The four non-gilled mushrooms extract exhibited DPPH, NO2, and H2O2 free radical scavenging activities. G. lucidum methanolic extract has the highest effect on free radicals in comparison to hexane effect. Conclusion: All the isolated four non-gilled mushrooms showed good antioxidant potential, and it can be concluded that these mushrooms are not only consumed but also have a wide range of medicinal properties which must further explode for future use.